1901 Fla. Laws 57 - (:unkn) unknown (My University, 1901)
Ch. 4928: Amended 1893 Fla. Laws 71, ch. 4147 to include licensing for carrying concealed handguns. Violators fined one hundred dollars or jailed for thirty days.
Keywords: CARRY - CONCEALED